Evaluasi Adsorben Sabut Kelapa untuk Pemisah Minyak dan Lemak pada Air Limbah Domestik - Puspa, Kinanti; Rosdiana, Rosdiana; Adami, Aryani (Universitas Muhammadiyah Kendari, 2024)
Oils and fats, which act as the main components in food, are often found in domestic wastewater and are difficult for bacteria to break down, so they have the potential to disrupt aquatic ecosystems. Adsorption with natural fiber-based materials, such as coconut fiber, is a common approach for removing oil and grease from household wastewater. The aim of this research is to analyze the effectiveness of coconut fiber as an adsorbent in separating oil and fat in domestic wastewater. The research began with taking samples of domestic wastewater from a restaurant in Kendari City, followed by making an adsorption tool and preparing coconut fiber adsorbent and ending with adsorption testing. The research found fluctuations in the oil and fat content of restaurant wastewater before and after the adsorption procedure. Adsorption was carried out using adsorbent media 30 cm thick with contact times of 60, 80 and 100 minutes. The decrease in the effectiveness of contact time of 60 minutes, 80 minutes, and 100 minutes was 20.12%, 7.59%, and 10.68% respectively. According to the research results, coconut fiber is not effective as an adsorption medium for absorbing oil and fat in domestic wastewater. It is recommended to carry out further research by carrying out pretreatment of the coconut fiber adsorbent first so that the adsorption process can reach optimum conditions.